Morphine‐induced respiratory depression is independent of β‐arrestin2 signalling. (17th February 2020) - Kliewer, Andrea; Gillis, Alexander; Hill, Rob; Schmiedel, Frank; Bailey, Chris; Kelly, Eamonn; Henderson, Graeme; Christie, Macdonald J.; Schulz, Stefan
Abstract : Background and Purpose: GPCRs can signal through both G proteins and β‐arrestin2. For the μ‐opioid receptor, early experimental evidence from a single study suggested that G protein signalling mediates analgesia, whereas β‐arrestin2 signalling mediates respiratory depression and constipation. Consequently, for more than a decade, much research effort has been focused on developing biased μ‐opioid agonists that preferentially target G protein signalling over β‐arrestin signalling, as it was believed that such drugs would be analgesics devoid of respiratory depressant activity. However, the prototypical compounds that have been developed based on this concept have so far failed in clinical and preclinical development. Experimental Approach: The present study was set up to re‐examine opioid‐induced respiratory depression in β‐arrestin2 knockout mice. To this end, a consortium was formed consisting of three different laboratories located in different countries to evaluate independently opioid‐induced respiratory depression. Key Results: Our consensus results unequivocally demonstrate that the prototypical μ‐opioid agonist morphine (3.75–100 mg·kg −1 s.c. or 3–30 mg·kg −1 i.p.) as well as the potent opioid fentanyl (0.05–0.35 mg·kg −1 s.c.) do indeed induce respiratory depression and constipation in β‐arrestin2 knockout mice in a dose‐dependent manner indistinguishable from that observed in wild‐type mice. Conclusion and Implications: Our findings do not support the original suggestion that β‐arrestin2 signalling plays a key role in opioid‐induced respiratory depression and call into question the concept of developing G protein‐biased μ‐opioid receptor agonists as a strategy for the development of safer opioid analgesic drugs.